EFEITO DE DIETA “LOW CARB” E EXERCÍCIOS EM MULHERES COM SOP: UM ESTUDO RANDOMIZADO SOBRE QUALIDADE DE VIDA E RISCO CARDIOVASCULAR - Henrique Amelio Alves Ferreira Ferreira , Pedro; Aparecida Vieira Machado , Alessandra; Nantes Stein , Alexander; Luiz da Silva , Vitor; Prates Lourenço, Eduarda (ANAIS DO ENIC, 2026)
-